2014
DOI: 10.1088/0953-8984/26/28/326001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance of the high-pressure ferromagnetic phases (GaSb)2M (M=Cr,Mn)

Abstract: For the first time magnetoresistance of the ferromagnetic high-pressure phases (GaSb)2M (M=Cr,Mn) has been measured in a wide range of temperature and magnetic field. It was found that the magnetic field dependencies of resistivity of both systems contain several contributions, including relatively smaller s-d exchange (Yosida-type) components in low fields and a quadratic positive term (PMR) in the low temperature region. The magnitude of the predominated negative term (NMR), which can be attributed to the qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Recently, Pronin et al and Kondrin et al found FM Cr-GaSb phase synthesized under high pressure. 17,18) However, the origin of ferromagnetism and electronic structures in Cr-GaSb are still unclear. In this paper, the electronic structures and magnetic properties in Cr doped GaSb are investigated systematically by the first-principles calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Pronin et al and Kondrin et al found FM Cr-GaSb phase synthesized under high pressure. 17,18) However, the origin of ferromagnetism and electronic structures in Cr-GaSb are still unclear. In this paper, the electronic structures and magnetic properties in Cr doped GaSb are investigated systematically by the first-principles calculation.…”
Section: Introductionmentioning
confidence: 99%